Alien planets - World Book, Inc (Chicago, IL World Book, 2010)
An introduction to extrasolar planets, with information about their formation and characteristics. Includes diagrams, fun facts, a glossary, a resource list, and an index"--Provided by publisher
Includes bibliographical references (p. 62) and index
5 8
Keywords: Extrasolar planets -- Juvenile literature